ARQ-based spectrum sharing with multiple-access secondary system - Fang, Shu. (2013)
We consider a cognitive radio network in which a multiple-access secondary system coexists with an automatic repeat request (ARQ)-based primary system under heavy primary traffic. To achieve spectrum sharing without degrading the performance of the primary system, the secondary transmitters alternate between cooperation and access modes based on a credit system. In the cooperation mode, the secondary transmitters serve as potential relays among which the best one is selected to help forward the primary packet, thus accumulating credits. These credits will then allow the secondary transmitters to gain spectrum access by exploiting the ARQ mechanism of the primary system. Our results show that with a cluster of closely located secondary transmitters, the proposed spectrum sharing protocol achieves an equal average throughput for the primary system compared to the case without spectrum sharing, while providing access opportunities for the secondary system. Furthermore, by increasing the number of secondary transmitters or decreasing the distance between secondary transmitters and secondary receiver, an overall higher throughput can be achieved for the secondary system, without affecting the analytical results for the upper bounds of primary throughput under cooperation mode, and secondary throughput under access mode are also derived.